2017
DOI: 10.1016/j.mimet.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Stool antigen immunodetection for diagnosis of Giardia duodenalis infection in human subjects with HIV and cancer

Abstract: Human infection with the protozoan parasite Giardia duodenalis is one the most common parasitic diseases worldwide. Higher incidence rates of giardiasis have been reported from human subjects with multiple debilitating chronic conditions, including hypogammaglobulinemia and common variable immunodeficiency (CVID). In the current study, stool specimens were collected from 199 individuals diagnosed with HIV or cancer and immunocompetent subjects. The sensitivity of microscopy-based detection on fresh stool prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…In recent years, there is an increased rate of using stool antigen immunodetection-based assays for the detection of Giardia infections in humans, widely in diagnostic laboratories in both underdeveloped and developing countries and this is because of their higher sensitivity compared to conventional microscopic diagnostic methods. Antigen detection modalities have rapid diagnostic capabilities and comparable sensitivity and specificity to those of stool-based PCR methods for the diagnosis of giardiasis 5 .…”
mentioning
confidence: 99%
“…In recent years, there is an increased rate of using stool antigen immunodetection-based assays for the detection of Giardia infections in humans, widely in diagnostic laboratories in both underdeveloped and developing countries and this is because of their higher sensitivity compared to conventional microscopic diagnostic methods. Antigen detection modalities have rapid diagnostic capabilities and comparable sensitivity and specificity to those of stool-based PCR methods for the diagnosis of giardiasis 5 .…”
mentioning
confidence: 99%
“…In this study, tpi assemblage-specific PCR assays showed a high prevalence (45.2%) of mixed infection of A and B assemblage in Tehran isolates, but less than reported in Malaysia (64%) ( 36 ), although greater than in Belgium (32.4%) ( 32 ) using the same primers. Co-infection by assemblage A and B has been previously reported in Iran based on PCR-RFLP of the gdh locus ( 21 , 25 , 43 , 45 ).…”
Section: Discussionmentioning
confidence: 94%
“…8 Unlike in immunocompetent patients, microscopic detection of parasites in stool has low sensitivity in immunocompromised patients. 17 Furthermore, the fact that cysts are often excreted intermittently or sometimes released in numbers too small to be detected also decreases the sensitivity of this test. 12 In immunocompromised patients with HIV, stool antigen immunodetection-based modalities have been shown to have higher sensitivity than stool microscopy.…”
Section: Giardiasismentioning
confidence: 99%
“…12 In immunocompromised patients with HIV, stool antigen immunodetection-based modalities have been shown to have higher sensitivity than stool microscopy. 17 However, in some cases confirmatory testing via duodenal biopsy and aspiration might be needed in patients having persistent GI symptoms. 9 Treatment of giardia is typically metronidazole, nitazoxanide, or paromomycin.…”
Section: Giardiasismentioning
confidence: 99%